2019
DOI: 10.3390/nu11112562
|View full text |Cite
|
Sign up to set email alerts
|

Combined Supplementation with Glycine and Tryptophan Reduces Purine-Induced Serum Uric Acid Elevation by Accelerating Urinary Uric Acid Excretion: A Randomized, Single-Blind, Placebo-Controlled, Crossover Study

Abstract: The authors previously confirmed the serum uric acid-lowering effects of the combination of glycine and tryptophan in subjects with mild hyperuricemia. This study examined whether combined supplementation with glycine and tryptophan suppressed the elevation in serum uric acid levels caused by purine ingestion and accelerated urinary uric acid excretion in subjects with lower urate excretion using a randomized, single-blind, placebo-controlled, crossover clinical trial design. Healthy Japanese adult males with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…The current study demonstrated that the combined oral administration of glycine and tryptophan significantly elevated the eGFR of healthy participants. This mixture also decreased the serum uric acid levels, consistent with our previous reports[20,21]. No differences were observed in the effect of glycine and tryptophan supplementation between males and females, although the previous studies included mostly male participants.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…The current study demonstrated that the combined oral administration of glycine and tryptophan significantly elevated the eGFR of healthy participants. This mixture also decreased the serum uric acid levels, consistent with our previous reports[20,21]. No differences were observed in the effect of glycine and tryptophan supplementation between males and females, although the previous studies included mostly male participants.…”
supporting
confidence: 90%
“…In our two previous clinical trials, the oral administration of the combined dose of glycine and tryptophan led to a decreased concentration of serum uric acid because of the increased urate excretion into the urine [20,21]. A recent prospective cohort study suggested that serum uric acid levels are independently associated with the incidence of impaired renal function and renal progression [22], and a meta-analysis reported that uric acid-lowering therapy effectively regards CKD progression [23].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The major amino acids of kidney bean protein were Glu, Asp, Leu, Lys, Val, and Phe. It was previously confirmed that the combined supplementation with glycine and tryptophan significantly reduced the elevated serum uric acid levels after purine ingestion (Oshima, Shiiya, & Nakamura, 2019). Dipeptide Asp‐Asn could inhibit relevant enzyme activity and activate some endogenous XO inhibitors, presenting strong uric acid lowering activity (Murota et al., 2014).…”
Section: Resultsmentioning
confidence: 72%
“…A previous report showed that the purified XO inhibitor from Pleurotus ostreatus was a tripeptide and the amino acid sequence was phenylalanine–cysteine–histidine (Jang et al., 2014). It was also found that the combination of glycine and tryptophan could reduce the purine‐induced serum uric acid elevation by accelerating uric acid excretion (Oshima et al., 2019). In a research of milk‐derived dipeptides, tryptophan was confirmed to have a negative effect on XO activity.…”
Section: Resultsmentioning
confidence: 99%